1/3*(cosx)^(-3)-(cosx)^(-1)+C
∫tan^3secx dx
=∫(sinx)^3/(cosx)^4 dx
=-∫ (sinx)^2/(cosx)^4 dcosx
=-∫(1-(cosx)^2)/(cosx)^4 dcosx
=1/3*(cosx)^(-3)-(cosx)^(-1)+C
扩展资料
不定积分的公式
1、∫ a dx = ax + C,a和C都是常数
2、∫ x^a dx = [x^(a + 1)]/(a + 1) + C,其中a为常数且 a ≠ -1
3、∫ 1/x dx = ln|x| + C
4、∫ a^x dx = (1/lna)a^x + C,其中a > 0 且 a ≠ 1
5、∫ e^x dx = e^x + C
6、∫ cosx dx = sinx + C
7、∫ sinx dx = - cosx + C
8、∫ cotx dx = ln|sinx| + C = - ln|cscx| + C
9、∫ tanx dx = - ln|cosx| + C = ln|secx| + C
10、∫ secx dx =ln|cot(x/2)| + C = (1/2)ln|(1 + sinx)/(1 - sinx)| + C =
int(tanx^3secxdx)=int(tanx^2secxtanxdx)=int(tanx^2dsecx)=int[(secx^2-1)dsecx]=secx^3/3-secx+c
其中int代表积分号。
S tan^3secx dx=S (sinx)^3/(cosx)^4 dx=-S (sinx)^2/(cosx)^4 dcosx
=-S (1-(cosx)^2)/(cosx)^4 dcosx=1/3*(cosx)^(-3)-(cosx)^(-1)+C